Uptake and Efflux of Xenobiotic Transporter Substrates in Zebrafish Embryo Ionocytes - Gordon, Wei E. (Aquat Toxicol, 2019)
Ionocytes are specialized cells in the epidermis of embryonic zebrafish (Danio rerio) that play important roles in ion homeostasis and have functional similarities to mammalian renal cells. Here, we examined whether these cells might also share another functional similarity with renal cells, which is the presence of efflux transporter activities useful for elimination of toxic small molecules. Xenobiotic transporters (XTs), including the ATP-Binding Cassette (ABC) family, are a major defense mechanism against diffusible toxic molecules in aquatic embryos, including zebrafish, but their activity in the ionocytes has not previously been studied. Using fluorescent small molecule substrates of XT, we observed that specific populations of ionocytes uptake and efflux fluorescent small molecules in a manner consistent with active transport. We specifically identified a P-gp/ABCB1 inhibitor-sensitive efflux activity in the H(+)-ATPase-rich (HR) ionocytes, and show that these cells exhibit enriched expression of the ABCB gene, abcb5. The results extend our understanding of the functional significance of zebrafish ionocytes and indicate that these cells could play an important role in protection of the fish embryo from harmful small molecules.